ASPEK-ASPEK PSIKOLOGI DALAM NOVEL TETRALOGI LASKAR PELANGI KARYA ANDREA HIRATA - Sukirman (BASTRA : Jurnal Penelitian Pendidikan Bahasa dan Sastra, 2015)
Tetralogi Laskar Pelangi consisting of first novel "Laskar Pelangi", second "Sang Pemimpi", third "Edensor", and last "Maryamah Karpov".Tetralogi Laskar Pelangi many give picture about culture background in location occupied or than just visited by leaders in him. Literature Psychology approach could explain on spiritual and research nature under author aware. Sastra psychology is a art that present situation does not hold water and a events that fantastik.People author have to have certain expertise to can give aesthetic values use psychological aspects. Karya Sastra Novel Tetralogi Laskar Pelangi Psychology aspect will provide new repertoire for sartra research development in this country. Besides will also reveal aspects that all this time become power a belleslettres that attract the beneficiary interest. In peneltian explain on spiritual aspects to leaders in tetralogi Laskar Pelangi belleslettres by know and decipher those characters by descriptive. Research divided into three stage, namely: (1) data collection, data processing, data.Penelitian interpretation on psychological next will direct to human psychology system existence to interpret, memaknai, assess, and take action against self existence and environment.